Magnesium Induced Nucleophile Activation in the Guanylyltransferase mRNA Capping Enzyme - Swift, Robert V. (2012)
The messenger RNA guanylyltransferase, or mRNA capping enzyme, co-transcriptionally caps the 5′-end of nascent mRNA with GMP during the second in a set of three enzymatic reactions that result in the formation of an N7-methyl guanosine cap during mRNA maturation. The mRNA capping enzyme is characterized, in part, by a conserved lysine nucleophile that attacks the alpha-phosphorous atom of GTP, forming a lysine-GMP intermediate. Experiments have firmly established that magnesium is required for efficient intermediate formation, but have provided little insight into the requirement’s molecular origins. Using empirical and thermodynamic integration pKa estimates, along with conventional MD simulations, we show that magnesium binding likely activates the lysine nucleophile by increasing its acidity and by biasing the deprotonated nucleophile into conformations conducive to intermediate formation. These results provide additional functional understanding of an important enzyme in the mRNA transcript life cycle and allow functional analogies to be drawn that affect our understanding of the metal dependence of related superfamily members.